Answer:
![y=x^2+4x-21](https://img.qammunity.org/2023/formulas/mathematics/college/vy51vuxdvh2x8y9pmte1sst1cqmkknglib.png)
Explanation:
![\boxed{\begin{minipage}{6 cm}\underline{Factored form of a quadratic equation}\\\\$y=a(x-p)(x-q)$\\\\where:\\ \phantom{ww}$\bullet$ $p$ and $q$ are the zeros. \\ \phantom{ww}$\bullet$ $a$ is the leading coefficient.\\\end{minipage}}](https://img.qammunity.org/2023/formulas/mathematics/college/znoslldivy28snmfyjmu1h570okjvhg3sv.png)
Given zeros:
Substitute the given zeros into the formula:
![\implies y=a(x-(-7))(x-3)](https://img.qammunity.org/2023/formulas/mathematics/college/49ggcqcqe16hlfq8to7la82hpp1tchtg5z.png)
![\implies y=a(x+7)(x-3)](https://img.qammunity.org/2023/formulas/mathematics/college/h5a7ooaxxdhh7wzdvhg59adqrlu00zfzb8.png)
The value of "a" will not change the zeros, therefore let "a" equal any value:
![\implies y=1(x+7)(x-3)](https://img.qammunity.org/2023/formulas/mathematics/college/cvii56uk7qtdf0cuq3enev0sofcsjdbw8l.png)
![\implies y=(x+7)(x-3)](https://img.qammunity.org/2023/formulas/mathematics/college/y7jhx0qp33fqjtw3pgv2ucnf8ytcjv55nv.png)
Standard form of a quadratic equation:
![\boxed{y=ax^2+bx+c}](https://img.qammunity.org/2023/formulas/mathematics/college/keapaa98zc6583nr8q1ao7ydiarbz4j7kz.png)
Therefore, to write the equation in standard form, expand the brackets and simplify:
![\implies y=x(x-3)+7(x-3)](https://img.qammunity.org/2023/formulas/mathematics/college/c8yrqtysixlv0z76hnqtnnmrfx7z5r7znz.png)
![\implies y=x^2-3x+7x-21](https://img.qammunity.org/2023/formulas/mathematics/college/1srn3xpyi0zqv49gu3081dqzq0dpgr1cvh.png)
![\implies y=x^2+4x-21](https://img.qammunity.org/2023/formulas/mathematics/college/l9tqhg1rpyp1dr6vr7cxj697l0odemvaeu.png)